Dampak Keterlibatan Penyandang Disabilitas Dalam Operasional Kafe Terhadap Kepuasan Pelanggan Dan Persepsi Masyarakat Inklusi Sosial (Studi Penelitian : Sunyi, House Of Coffeee & Hope Jakarta) - Badrudin, Muhammad; Parantika, Asep (Peneliti.net, 2024)
People with disabilities face socio-economic barriers, including limited access to resources, and 8.5% of Indonesia's population, including 22.97 million elderly people, need support. Cafés can contribute to social inclusion by providing social spaces for people with disabilities to gather and share experiences. This research uses qualitative research to understand the phenomenon of behavior, motivation, and action. Integrating people with disabilities in café operations can create a more inclusive environment, expand opportunities, and stimulate positive changes in people's perceptions of social inclusion. Social engagement, especially in coffee shop operations, can positively impact customer happiness and overall image. However, challenges such as negative attitudes, limited access to information and services, and socioeconomic issues must be overcome.